Governments spending and growth nexus with nonlinear adjustments: re-examining the Croatian and Slovenian case. Issue 1 (1st January 2018) - Bošnjak, Mile
Abstract: The objective of this paper is to analyze the governments spending - economic growth nexus and examine the asymmetries in the adjustment process between the two in the Croatian and Slovenian economy. The baseline relationship model between the variables of interest is grounded on the assumption of Wagner's Law and Keynesian hypothesis. A possible nonlinear asymmetric effect of governments spending and GDP toward their long-run equilibrium is tested for each case. The test results indicate the presence of nonlienarity in the relationship between public spending and GDP in Croatia and Slovenia as well. Eventually, country specific threshold cointegrating relationship between the considered variables are estimated and tested. The results reveal well suited threshold vector error correction model with significantly different error correction adjustments in normal and stress regimes for each of the two sample country.